The Future of Data Warehousing: Trends, Technologies, and Challenges in the Era of Big Data, Cloud Computing, and Artificial Intelligence - Srikanth Gangarapu,; Vishnu Vardhan Reddy Chilukoori, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article explores the future of data warehousing, discussing emerging trends, technologies, and challenges shaping the landscape of data management and analytics in the era of big data, cloud computing, and artificial intelligence. It delves into topics such as the rise of cloud data warehouses, the increasing adoption of artificial intelligence and machine learning in data warehousing for advanced analytics and automation, the growing importance of data governance, privacy, and security in the face of evolving regulations, and the need for real-time data processing and analytics to support agile decision-making. The article also discusses the challenges faced by organizations in adopting and implementing these new technologies, such as the need for skilled personnel, the complexity of data integration from diverse sources, the cost of infrastructure and migration, and the ethical considerations surrounding the use of AI and ML in data warehousing. It concludes by highlighting the potential of data warehousing to drive innovation, improve operational efficiency, and gain a competitive advantage in the digital age.
Keywords: Cloud Data Warehousing; Artificial Intelligence in Analytics; Real-time Data Processing; Data Governance and Security; Data Integration Challenges